FACTORS AFFECTING THE LOW IMPLEMENTATION OF STIMULATION DETECTION OF EARLY GROWTH AND DEVELOPMENT INTERVENTIONS (SDIDTK) IN COMMUNITY HEALTH CENTRE IN BENGKULU CITY - Mariati Mariati; Anissa Aprilianthy; Elly Wahyuni; Ratna Dewi; Rina Rina (Poltekkes Kemenkes Bengkulu, 2022)
The early intervention detection stimulation program for Stimulation, Detection, and Early Intervention of Growth and Development or Stimulasi, Deteksi dan lntervensi Dini Tumbuh Kembang Anak (SDIDTK) is a comprehensive and quality child development program. SDIDTK success indicator in Bengkulu city is still 70.07%, which is not sufficient to achieve the indicator applied by the Indonesian Ministry of Health, which is 90% of the total population. This study aimed to determine the factors that influence the low implementation of SDIDTK at the Community Health Centre in Bengkulu City. This study used a qualitative research method with in-depth interviews. Informants were the head of the community health centres or Pusat Kesehatan Masyarakat (Puskesmas), coordinator midwives, and midwives who handled the SDIDTK program at the Penurunan, Anggut Atas, and Lingkar Barat Community Health Centre. This study found that the number of health workers in 1 puskesmas was lacking, SDIDTK program holders in 2 Puskesmas had not received training, in 2020, 2 puskesmas did not run integrated healthcare centres or Pos Pelayanan Terpadu (Posyandu) and SDIDTK due to COVID-19. The availability of facilities and infrastructure was quite good, but it had not been used optimally by health workers. There was already a budget from the Health Operational Assistance or Bantuan Operasional Kesehatan (BOK) for health workers' transportation when they visited the field. It is expected that puskesmas will provide opportunities for health workers, especially midwives, to receive training in the implementation of SDIDTK.